Figure 6 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 6. Euplotes petzi nov. spec. from life (A, C, D) and after protargol impregnation (B, E–G) (C, D, G; after Petz, Song and Wilbert 1995). (A, D) Specimens found in 2006 population (A) and 1995 population (D), note the different lengths of most ciliary organelles. (B) Different shapes of macronucleus. (C) To show the dorsal ridges (arrows). (E, F) Ventral and dorsal view of a specimen from 2006 population. (G) Dorsal view of a specimen from the population studied by Petz et al. 1995. CC, caudal cirri; DK, dorsal kineties; FVC, frontoventral cirri; Ma, macronucleus; MC, marginal cirrus; Mi, micronucleus; TC, transverse cirri. Scale bars: 30 Mm. : Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 1000, DOI: 10.1080/00222930701877540, http://zenodo.org/record/5219160